Correlation between Body Mass Index to Hypertension in A Rural Area in East Java - Kurniawan, Alvin Hartanto; Suwandi, Benedictus Hanjaya; Prakoso, Dicky Teguh; Moksidy, Reynaldy Cliftianto; Talitha, Irma; Anggraeni, Maharani Kartika; Zulkifli, Danang (Universitas Muhammadiyah Yogyakarta, 2021)
Hypertension is one of the most commonly encountered problems in primary health care and a major risk factor for other lethal diseases. Obesity, another arising problem in developing and developed countries, is another major risk factor for metabolic disease. However, studies about both diseases and their intercorrelation in rural areas are still limited. Therefore, we conducted this study to investigate the correlation between body mass index (BMI) and blood pressure in a rural area. This study was an observational, cross-sectional study performed in outpatients at Community Health Care of Ngronggot, a rural area in East Java for one month with inclusion criteria aged 18 years old, systole blood pressure (SBP) â‰¥140 and/or diastole blood pressure (DBP) â‰¥90, or a history of anti-hypertensive treatment. Information including age, gender, SBP, DBP, mean arterial pressure (MAP), body weight, and height was collected and calculated for its distribution and correlation using the Spearman rank-order correlation test. There were 201 subjects in this study, 65.7% of which were female, while 34.3% of which are male, and the median age was 59 years old. We also found that more than 60% of our participants were overweight and obese. The results of the Spearman test showed that BMI significantly correlated with SBP (p=0.029), DBP (p=0.016), and MAP (p=0.008). In conclusion, BMI had a positive correlation with blood pressure, and obesity was prevalent in our rural area population.